Analisis Tingkat Kesadaran ASN Terhadap Disiplin Kerja Di BPPRD Provinsi Sumatera Utara - Putri, Adella; Harahap, Muhammad Ihsan (Balance : Jurnal Akuntansi dan Manajemen, 2022)
Discipline is an attitude in developing something properly. The discipline itself is compliance, order, and regularity related to all existing activities. Work discipline attitude is very much needed and needed in character development. Every individual who develops this disciplined attitude in each field of work will obtain maximum and optimal work results. State Civil Apparatus or ASN is a term for a professional group of employees who work in government agencies both at the central and regional levels. This study will be directly related to the discipline of the ASN in the Regional Tax and Levy Management Agency of North Sumatra Province. How are the sanctions and what penalties are applied in the violation of existing discipline and of course by the existing rules. Obstacles faced by an ASN in improving ASN Discipline are the lack of firmness of sanctions given by authorized officials and the erosion of ASN Discipline. The solution is to have strict sanctions/actions if an ASN is proven to have committed a disciplinary violation intending to provide a deterrent effect and shock therapy so that other ASNs do not imitate or commit more serious violations